GE_GERICHTE C/24719/2013 vom 28. August 2017 - GE Cour de justice (2017)
HEURES DE TRAVAIL SUPPLÉMENTAIRES ; SALAIRE ; INTERPRÉTATION(SENS GÉNÉRAL) ; VACANCES | CPC.317; CO.321E; CO.322; CPC.227; CO.329A